Cloud modeling tool for problem solving : Development of scaffolding features - Yudho Ahmad Diponegoro. (2012)
Pres-On as a modeling tool with dynamic simulation feature is meant to be a platform for the learning process that involves conceptual change. Problem solving activity is used as a method to achieve conceptual change. The problem solving utilizes some case studies based on the real world system.